2021
DOI: 10.1021/acs.jpcc.1c01804
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Sensing of Au Nanoparticles Manipulated by an Optical Vortex

Abstract: Recently, electrical sensing techniques of single small objects, such as nanoparticles, viruses, and biomolecules, have attracted much attention. However, fine-tuning of a sensing section is required to achieve high throughput and high precision. Herein, we propose a novel method to improve the measurement accuracy of electrical signals using a double-nanoslit structure exposed to an optical vortex. A small Au particle with a diameter of 200 nm dispersed in a phosphate-buffered saline solution is optically tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Then, the electric field and the pressure gradient usually become strongest at a narrow sensing section and cause an increase in the transport speed of target objects, which deteriorates the measurement accuracy. Some researchers have proposed novel methods to overcome these problems by tuning the conditions of liquids. ,,, Recently, multiple pore structures and optically driven orbital motions of single particles , were applied to improve throughput and measurement accuracy. On the other hand, such nanostructures cause the transport speed outside the sensing section to decrease because electric fields and liquid flows far from the sensing section are too weak to drive target objects forward.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the electric field and the pressure gradient usually become strongest at a narrow sensing section and cause an increase in the transport speed of target objects, which deteriorates the measurement accuracy. Some researchers have proposed novel methods to overcome these problems by tuning the conditions of liquids. ,,, Recently, multiple pore structures and optically driven orbital motions of single particles , were applied to improve throughput and measurement accuracy. On the other hand, such nanostructures cause the transport speed outside the sensing section to decrease because electric fields and liquid flows far from the sensing section are too weak to drive target objects forward.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the knowledge obtained in our previous studies, ,,, the relationship between the particle transport and electrical signals is investigated. For the fundamental study, electrical sensing is synchronized with optical observation using a polystyrene particle with a diameter of approximately 500 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Tsuji et al experimentally and numerically investigated the collective orbital motion of plural PS microparticles driven by an optical vortex by considering the hydrodynamic interactions between particles. We have demonstrated that optical forces can be tuned to manipulate small objects for various applications. , Recently, our research group , reported that the electrical measurement accuracy of micro- and nanoparticles is drastically improved when using an optical vortex that iteratively brings target particles into a double-slit test section. In the previous studies, we succeeded in manipulating single PS particles and gold nanoparticles (Au NPs) in a narrow space.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that optical forces can be tuned to manipulate small objects for various applications. , Recently, our research group , reported that the electrical measurement accuracy of micro- and nanoparticles is drastically improved when using an optical vortex that iteratively brings target particles into a double-slit test section. In the previous studies, we succeeded in manipulating single PS particles and gold nanoparticles (Au NPs) in a narrow space. However, the reproducible manipulation of single nanoparticles is challenging because of the large thermal fluctuations and the small optical forces, which are on the order of 10 –15 N (1 fN).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation